The ISWI and CHD1 chromatin remodelling activities influence ADH2 expression and chromatin organization. - Xella, B; Goding, C; Agricola, E; Di Mauro, E; Caserta, M (2006)
Nucleosome remodelling complexes play a key role in gene activation in response to environmental changes by driving promoter chromatin to reach an accessible configuration. They also mediate genome-wide chromatin organization, although their role in processes other than activation-related chromatin remodelling are poorly understood. The Saccharomyces cerevisiae ADH2 gene represents an excellent model for understanding the role of chromatin structure and remodelling in gene regulation. Following glucose depletion, highly positioned promoter nucleosomes are destabilized leading to strictly regulated kinetics of transcriptional activation. Nevertheless, no chromatin remodelling activities responsible for establishing or remodelling ADH2 chromatin structure have been identified to date. Here we show that the absence of the Isw1 and Chd1 ATP-dependent chromatin remodelling activities delays the maximal expression of ADH2 without impairing the chromatin remodelling that occurs upon activation. Instead, a destabilized chromatin structure on the ADH2 coding and termination region is observed in the absence of Isw1 or Chd1 in repressing conditions. The specific Isw1 complex involved in this nucleosome repositioning is Isw1b because the deletion of Ioc2 and Ioc4, but not of Ioc3, causes the same phenotype as the deletion of Isw1. Moreover, the lack of Chd1 combined with the absence of Isw1 and Isw2 impairs nucleosome spacing along the ADH2 gene, and genome-wide in S. cerevisiae. Thus, the ISWI and Chd1 remodelling factors are not only involved in transcription-related chromatin remodelling, but also are required to maintain a specific chromatin configuration across the yeast genome.